Lise 2”nci sınıf öğrencilerinin alanlarına göre, kişilik özellikleri, mesleki ilgileri ve akademik başarılarının incelenmesi - Karamustafa, Muhammed (My University, 2000)
In this study, a set of personality characteristics, career interests and academic achievements of the two group students in the different fields in the high schools and also the relationships between them which is mentioned above were investigated. The career interest was investigated by Kendini Değerlendirme Envanteri (KDE),while personality characteristic was measured by Adjective Check List (ACL) and academic achievement was established from their annual students reports. The sample was consisted of 342 subjects, 117 of which were from Science Department (Fen Bilimleri) 127 of which were from Turkish-Math Department (Türkçe -Matematik) 98 of which were from Department of Social Science(Sosyal Bilgiler). The following were concluded: 1-It was found that the first four personality characteristics were the same in all fields while the fifth one was different in Social Science than the other two. The first five personality characteristics were 1-creative personality 2-ideal self-esteem 3-dominance 4-personal harmony 5-endurance. In Social Science Department the fifth characteristic is different than the other departments. 2-It was also found that their career interests were related to the academic achievements in their fields' subjects. 3-It was found that some career interests make differences between the fields; Some career interests that make Science(Fen Bilgisi) differ from Turkish-Math (Türkçe-Matematik); 1-Numerical Ability 2-Basic Science Interest 3-Mechanical Interest Career interests that make Turkish-Math (Türkçe-Matematik) differ from Science(Fen Bilgisi); 1-Article Ability 2-Social Science Interest 3-Literatural Interest Career interests that make Science (Fen Bilgileri) are different from Social Science(Sosyal Bilgiler); 1-Numerıcal Ability 2-Ability of Dimensional Thought 3-Basic Science Interest 4-Mechanical Interest Career interests that make Social Science (Sosyal Bilgiler) differ from Turkish-Maths (Türkçe-Matematik); 1-Numerical Ability 2-Ability of Dimensional Thought 3-Basic Science Interest. As a result, the it is found that there is the significant relationships between the personality characteristics, career interests and academic achievements of the students in the high schools.

Tez de lise 2' nci sınıf öğrencilerinin alanlarına göre, kişilik özellikleri, mesleki ilgileri ve akademik başarıları incelenmektedir. Bu kapsamda Ünye ve Fatsa Liseleri ile Anadolu liselerinden 342 öğrenciye ulaşılmaktadır. Öğrencilerin alanlara göre dağılımı şu şekildedir: Fen Bilimleri 117 kişi, Türkçe - Matematik alanı 127 kişi, Sosyal Bilgiler alanı 98 kişi. Tezde kişilik özelliklerini belirlemek için Sıfat Tarama Listesi, mesleki ilgileri belirlemek için Kendini Değerlendirme Envanteri, akademik başarıları içinde birinci dönem not ortalamaları kullanılmıştır. Sonuç olarak; 1. Öğrencilerin öğrenim gördükleri alandaki öğrencilere atfettiği en yüksek puana sahip ilk beş kişilik özelliği Sosyal Bilgiler alanın beşinci kişilik özelliği hariç aynı çıkmıştır. 2.Alan dersleri ile alanın temsil eden mesleki ilgi ve yetenekler arasında birebir ilişki çıkmıştır. 3. Alanlara göre mesleki ilgi ve yeteneklerin farklılaştığı bulunmuştur.
Keywords: Eğitim, Orta-Türkiye; ÖĞRENCİLER-ORTA ÖĞRETİM